Cardiac involvement in creatine deficiency syndrome. (3rd October 2022) - Del Franco, A; Battini, R; Kusmic, C; Forini, F S; L'Abbate, S; Masotti, S; Musetti, V; Borrelli, C; Barison, A; Emdin, M; Vergaro, G
Abstract: Background: Previous reports have demonstrated electrocardiographic and echocardiographic abnormalities consistent with early-stage cardiomyopathy in patients with creatine transporter (CrT) deficiency, but cardiac involvement has never been accurately characterized. Purpose: To investigate the cardiac phenotype associated with creatine deficiency in a murine transgenic model and in patients with creatine deficiency syndrome (CDS). Methods: Wild type and transgenic CrT−/y mice (n=20) were serially evaluated in vivo by electrocardiogram (EKG) and echocardiography for six months, and ex vivo by histological and biochemical analyses. Nine patients with CDS (n=4 with L-arginine:glycine amidinotransferase - AGAT- deficiency, n=5 with CrT deficiency) underwent blood samples, including cardiac biomarkers, EKG, Holter monitoring, echocardiography and cardiac magnetic resonance (CMR). Results: Compared to wild type, CRT−/y mice showed a prolongation of QT interval (p=0.008) (Fig. 1), as well as significant reduction in cardiac ATP production from mitochondria (p<0.001) (Fig. 2). No differences were detected in the left ventricular systolic function, in terms of ejection fraction and global longitudinal strain, along the whole follow-up. Similarly, 3 patients with CrT deficiency also showed a prolonged QTc interval (median QTc 515 ms), while other 2 had a borderline QTc at Holter monitoring, while no tachyarrhythmias could be observed. No subject had abnormal systolic and diastolic function. At CMR, an increase of native T1 value was reported in the 4 subjects (median 1076 ms) with AGAT deficiency, 1 with an increase of extracellular volume matching with the detection of late gadolinium enhancement. Finally, subjects with AGAT deficiency showed an increase level of plasma norepinephrine. Familiar carriers (3 for AGAT and 1 for CrT) showed no notable cardiac functional alterations, except for QTc prolongation in 2 subjects. Conclusion: Prolonged QT interval is observed in the murine model and in subjects with CrT deficiency. Biohumoral signs of neurohormonal activation and an initial replacement fibrosis – the latter suggested by the increase of native T1 – are identified in subjects with AGAT deficiency, but their clinical significance remains to be determined. Funding Acknowledgement: Type of funding sources: None.